Exposure to respirable silica contributes to lower airway inflammation in asthmatic horses - Alessandra Romolo; Giulia Costa; Beatrice Sica; Giulia Memoli; Matteo Ardit; Francesco Di Benedetto; Donata Bellis; Silvana Capella; Elena Belluso; Michela Bullone (Journal of Veterinary Internal Medicine)
Abstract Background Respirable mineral particles can induce lower airway inflammation, but the role they play in asthma of horses is unknown. Objectives Respirable mineral particles, particularly respirable silica, are an overlooked determinant of chronic lung inflammation (asthma) in horses. Animals Twenty‐three horses from an equine hospital population: 11 moderately affected (MEA), 7 severely asthmatic (SEA), and 5 control horses free from respiratory clinical signs. Methods Prospective observational study. The quantity and quality of mineral particles found in bronchoalveolar lavage fluid (BALF) were characterized, with particular attention to silica content. Polarized light microscopy performed on cytospin slides identified intracellular birefringent particles as silica. Spectrometry‐based analysis performed on whole BALF determined total mineral and silica percentage and concentration. Group‐related differences in BALF mineral and silica load were investigated as well as associations with BALF cytology. Results Intracellular birefringent particles were increased in SEA vs MEA (median [interquartile range, IQR]), 12 [7] vs 4 [5] particles/30 high power fields [hpf], respectively; P = .01) and vs controls (4 [2] particles/30 hpf; P = .02). Total mineral concentration in BALF was similar between the groups studied, whereas silica concentration and percentage were increased in SEA vs MEA (1758 [887] particles/mL and 20 [10]% vs 867 [662] particles/mL and 8 [6]%; P = .009 and P = .001) and control group (355 [330] particles/mL and 6 [3]%; P = .0003 and P = .002). Silica load in BALF was associated with BALF neutrophilia in MEA and SEA. Conclusions and Clinical Importance Respirable silica is associated with neutrophilic lower airway inflammation in horses and might contribute to asthma development.